THE IMPLICATIONS OF THE GENERAL AGREEMENT ON TRADE IN SERVICES (GATS) TOWARD HIGHER EDUCATION ACCESSIBILITY OF POOR PEOPLE IN INDONESIA (Case Study: Higher Education Accessibility of Poor People in Indonesia) - Tiara Pramudita Sanaiscara N I (2014)
The General Agreement on Trade in Services (GATS) is one of the WTO agreements was formed to liberalize 12 the service sectors, including education. Through that regulation, Indonesia has to ratify and apply all commitments in the GATS. This means that Indonesia accepted that education,especially higher education to be liberalized.The controversial emerged when the impact of educational liberalization caused the human right violation. Basically, education was the right of all society. But, after the implementation of the GATS, higher education was commoditized to be owned only by small group of society who have capital. That phenomenon was caused by the increasing of higher education fees. The GATS commitments were implemented by the Indonesian government through making national law which accordance to those commitments. The changed education orientation was made by the government through several national laws, such as the law of state-owned legal entities, the law about foreign investment penetration, and the law about higher education. This is becoming a disease within society. The increasing of higher education fees caused poor people cannot access it at all. Finally, rich people will produce rich and smart descendants, while poor people will produce poor and stupid descendants. Even more, this condition was recognized by society as a norm. Keywords: the General Agreement on Trade in Services, liberalization of education, higher education fees, poor people.